Pemasaran Viral – Viral Marketing - James Rianto Situmorang (Business Administration Department - Universitas Katolik Parahyangan, 2010)
Viral marketing is an extremely powerful and effective form of internet marketing. Itis a new form of word-of-mouth through internet. In viral marketing, someone passeson a marketing message to someone else and so on. Viral marketing proposes thatmessages can be rapidly disseminated from consumer to consumer leading to largescale market acceptance. The analogy of a virus is used to described the exponentialdiffusion of information in an electronic environment and should not be confusedwith the negative connotation of a virus that is often associated with malicious dis-ruptive software programs. The viral spread of information can be compared to theanalogy of a sneeze, which typically releases approximately 2 million particles. Thereare many forms of viral marketing, such as: e-mail, e-books, blog, social networksites, and video.Keywords: internet, viral marketing, virus, word-of-mouth, e-mail, blog, socialnetworking sites, viral video, viral e-books